2006
DOI: 10.1176/appi.ajp.163.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Why Olanzapine Beats Risperidone, Risperidone Beats Quetiapine, and Quetiapine Beats Olanzapine: An Exploratory Analysis of Head-to-Head Comparison Studies of Second-Generation Antipsychotics

Abstract: Some sources of bias may limit the validity of head-to-head comparison studies of second-generation antipsychotics. Because most of the sources of bias identified in this review were subtle rather than compelling, the clinical usefulness of future trials may benefit from minor modifications to help avoid bias. The authors make a number of concrete suggestions for ways in which potential sources of bias can be addressed by study initiators, peer reviewers of studies under consideration for publication, and read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
220
0
14

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 397 publications
(240 citation statements)
references
References 86 publications
6
220
0
14
Order By: Relevance
“…Empirically, both Montgomery et al (2004) and ourselves find that biases do creep into the conclusions of RCTs of SGA (Heres et al, 2006). It is likely that a much greater degree of bias is present in the information the practitioners receive directly from industry (such as pharmaceutical representatives, industry-sponsored papers or symposia, Internet events, or speaker bureaus).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Empirically, both Montgomery et al (2004) and ourselves find that biases do creep into the conclusions of RCTs of SGA (Heres et al, 2006). It is likely that a much greater degree of bias is present in the information the practitioners receive directly from industry (such as pharmaceutical representatives, industry-sponsored papers or symposia, Internet events, or speaker bureaus).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed many studies in general medicine find that the sponsor's drug is superior to the comparator drug (Bodenheimer, 2000). Heres et al (2006) found that sponsors conclude their second-generation antipsychotics (SGAs) to be superior to their competitors' SGAs in 90% of the studies. In addition, Montgomery has reported similar results of SGAs vs first-generation antipsychotics (FGAs; Montgomery et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Results from positive trials and from favorable analyses are more likely to be published than results unfavorable to sponsors. [6][7][8] Compared with nonindustry-funded trials, pharmaceutical industry-funded studies more often yield results or conclusions in support of the sponsor's drug, [9][10][11][12][13][14][15][16] and authors' relationships with drug manufacturers have been linked to favorable assessments of drug efficacy and safety. [17][18][19][20] As a result, increased emphasis has been placed on the transparent disclosure of COI.…”
Section: Onflicts Of Interest (Cois)mentioning
confidence: 99%
“…However, federal supervision of the pharmaceutical industry is mainly concerned with study design and conduct and not so much with publications. Publications of study results by the pharmaceutical industry may have a certain bias (Heres et al 2006), so that demands for a respective ''disclosure'' are completely justified. However, one has to admit that not only publications of studies performed by the pharmaceutical industry can be biased.…”
Section: Declaration Of Conflicts Of Interest In Scientific Publicationsmentioning
confidence: 99%